Are patient falls in the hospital associated with lunar cycles? A retrospective observational study - Geest Sabina De; Joos Franco; Schwendimann René; Milisen Koen (BMC, 2005)
Abstract Background Falls and associated negative outcomes in hospitalized patients are of significant concerns. The etiology of hospital inpatient falls is multifactorial, including both intrinsic and extrinsic factors. Anecdotes from clinical practice exist in which health care professionals express the idea that the number of patient falls increases during times of full moon. The aim of this study was to examine in-hospital patient fall rates and their associations with days of the week, months, seasons and lunar cycles. Methods 3,842 fall incident reports of adult in-patients who fell while hospitalized in a 300-bed urban public hospital in Zurich, Switzerland were included. Adjusted fall rates per 1'000 patient days were compared with days of the week, months, and 62 complete lunar cycles from 1999 to 2003. Results The fall rate per 1000 patient days fluctuated slightly over the entire observation time, ranging from 8.4 falls to 9.7 falls per month (P = 0.757), and from 8.3 falls on Mondays to 9.3 falls on Saturdays (P = 0.587). The fall rate per 1000 patient days within the lunar days ranged from 7.2 falls on lunar day 17 to 10.6 falls on lunar day 20 (P = 0.575). Conclusion The inpatient fall rates in this hospital were neither associated with days of the week, months, or seasons nor with lunar cycles such as full moon or new moon. Preventive strategies should be focused on patients' modifiable fall risk factors and the provision of organizational conditions which support a safe hospital environment.